LINKING MINDFULNESS WITH ORGANIZATIONAL EFFECTIVENESS THROUGH EMOTIONAL REGULATION AND EMOTIONAL INTELLIGENCE: A CONCEPTUAL STUDY - Ganguly, Madhurima; Chakraborty, Tanusree; Deb, Mithila; Saha, Somrita; Mukherjee, 5Sanchali (International Journal of Psychosocial Rehabilitation, 2020)
Mindfulness is an adaptable condition of consciousness that includes open and responsive interest and consciousness of both one’s inward state and the outside world (Brown & Ryan, 2003; Brown, Ryan, & Creswell, 2007). This chapter reflects upon how mindfulness adds precision and detail description to recent knowledge and instigates more authentic contact with life, thus leading to enhancing self-regulation of individuals leading to emotional regulation. Emotional regulation helps an individual to gain better clarity of perspectives and an effective control over any satiation in an organization as well as in domestic front. Focusing upon the non- judgmental facet of mindfulness, the chapter draws upon how one can increase exact perception of their and other‟s emotion, leading o emotional intelligence. It also assesses the connection between emotional intelligence, mindfulness and subjective well-being of an individual leading to effective development of personality of an individual and their performance. It also discusses about the positive behavioral outcomes of individuals in an organization with high emotional intelligence and mindfulness. It also discusses the efficacy of mindfulness training to increase emotional intelligence and the benefits of emotional intelligence like enhanced positive affect and reduced negative affect.It also sheds light on how mindfulness contributes towards individual effectiveness and organizational performance and sustainability.